An investigation into the problems related to the adjustment of beginning-teachers leading to the development of an induction programme - Algie, Rowan Craig (Rhodes University, Faculty of Education, Department of Education, 1983)
There is little doubt that there is a widespread concern that the transition from the supportive environment of the training institution where mistakes are expected, self criticism is encouraged and both tutorial guidance and peer group friendship are readily available into a situation where professional and personal responsibilities are profoundly altered, where the methods used, the progress of the pupils, their parents' expectations, the working relationship with colleagues are now permanent responsibilities. This transition can be traumatic for some and a considerable ordeal for many.--Chapter 1, p. 10.
Keywords: Teachers, Probationary -- South Africa Teaching -- South Africa